2000
DOI: 10.1021/bi992187g
|View full text |Cite
|
Sign up to set email alerts
|

Threonine 201 in the Diiron Enzyme Toluene 4-Monooxygenase Is Not Required for Catalysis

Abstract: The diiron enzyme toluene 4-monooxygenase from Pseudomonas mendocina KR1 catalyzes the NADH- and O(2)-dependent hydroxylation of toluene. A combination of sequence alignments and spectroscopic studies indicate that T4MO has an active site structure closely related to the crystallographically characterized methane monooxygenase hydroxylase. In the methane monooxygenase hydroxylase, active site residue T213 has been proposed to participate in O(2) activation by analogy to certain proposals made for cytochrome P4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 55 publications
7
51
1
Order By: Relevance
“…A direct transfer of a proton to a peroxo intermediate or a positioning of water for this transfer have been proposed for the conserved Thr residue (27), and the participation of Thr-201 in orientation of HOH5 is consistent with the latter role in T4moH. Because mutagenesis showed that Thr-201 was not essential for steady-state catalysis (28), this residue may also participate in other steps in the reaction cycle, such as stabilization of the rearranged conformation for electron transfer.…”
Section: Resultsmentioning
confidence: 73%
“…A direct transfer of a proton to a peroxo intermediate or a positioning of water for this transfer have been proposed for the conserved Thr residue (27), and the participation of Thr-201 in orientation of HOH5 is consistent with the latter role in T4moH. Because mutagenesis showed that Thr-201 was not essential for steady-state catalysis (28), this residue may also participate in other steps in the reaction cycle, such as stabilization of the rearranged conformation for electron transfer.…”
Section: Resultsmentioning
confidence: 73%
“…The rotameric conformation of this Asn also changes with the active site oxidation state; it points inward toward the diiron center in the mixed-valent and reduced forms and away from it when the iron atoms are oxidized ( Figure 5B) (48,49). Mutagenesis studies on TMOs suggest that the Thr is not essential for catalysis under steady state conditions (60), whereas the Asn is important for turnover and protein component interactions. 5 The positions of this pair of Thr and Asn residues in both protomers from the native and SeMet PHH structures differ significantly from what has been observed for oxidized, reduced, and mixed-valent MMOH (8,46,48,49) as well as for oxidized and Mn 2+ -substituted ToMOH (9,57).…”
Section: Conserved Active Site Residues and Changes In Helix Ementioning
confidence: 99%
“…strain JS150 have been predicted by Pikus et al (25). The T201 residue encoded by tmoA in T4MO has been studied by saturation mutagenesis, and T4MO Q141C, Q141V, I180F, and F205I mutants with mutations in tmoA have been studied previously by using site-directed mutagenesis (24,25). For oxidation of m-xylene by the Q141C T4MO mutant, 3-methylbenzyl alcohol formation increased sixfold from 2.2% to 11.7%, and for p-xylene oxidation the product distribution completely switched to 2,5-dimethylphenol (78%) from 4-methylbenzyl alcohol (22%).…”
mentioning
confidence: 99%